Development and release in the Philippines of sweetpotato variety 'NSIC Sp-31' - Carpena, Azucena L.; Manguiat, Proceso; del Rosario, Edwin E.; Lalusin, Antonio G.; Gueco, Lavernee S.; Reaño, Consorcia E.; Rodriguez, Felicito M.; Quilloy, Reynaldo B. (2009)
'NSIC Sp-31' (Registry No. NSIC 2005 Sp 31) sweetpotato [Ipomoea batatas (L.) Lam.] variety is an offspring of the cross produced in 1999 at the Crop Science Cluster - Institute of Plant Breeding, College of Agriculture, University of the Philippines Los Baños (CSC-IPB, CA, UPLB) between recommended local sweetpotato variety 'UPL Sp-3' and a registered Chinese variety Jinshan 1255, designated as SG99-09-02. The genotype was evaluated from the 2001 wet season up to the 2004-2005 dry season, which included two seasons each of preliminary and general/advanced trials at UPLB and two seasons of regional trials in eight locations. NSIC Sp-31 has high root yield potential (17 t ha -1), high root dry matter (33%) and starch (24%) contents, good eating quality and resistance to scab disease under field conditions. NSIC Sp-31 was officially approved for release by the National Seed Industry Council (NSIC) on 5 June 2006.
Keywords: Sweet potatoes--Varieties.